2019
DOI: 10.1002/cbic.201800813
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Based Specific Detection and Inhibition of Monoamine Oxidases and Their Applications in Central Nervous System Diseases

Abstract: Monoamine oxidases (MAOs) are the enzymes that catalyze the oxidation of monoamines, such as dopamine, norepinephrine, and serotonin, which serve as key neurotransmitters in the central nervous system (CNS). MAOs play important roles in maintaining the homeostasis of monoamines, and the aberrant expression or activation of MAOs underlies the pathogenesis of monoamine neurotransmitter disorders, including neuropsychiatric and neurodegenerative diseases. Clearly, detecting and inhibiting the activities of MAOs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 128 publications
0
8
0
Order By: Relevance
“…It brought to light the role of monoamine oxidase enzymes in the pathologies of both types of diseases, making these enzymes a common link between depression and neurodegenerative diseases [5]. In recent years, many new studies have confirmed that monoamine oxidase enzymes play an important role in developing both depression and neurodegenerative diseases [14].…”
Section: Monoamine Oxidase Pathwaysmentioning
confidence: 99%
“…It brought to light the role of monoamine oxidase enzymes in the pathologies of both types of diseases, making these enzymes a common link between depression and neurodegenerative diseases [5]. In recent years, many new studies have confirmed that monoamine oxidase enzymes play an important role in developing both depression and neurodegenerative diseases [14].…”
Section: Monoamine Oxidase Pathwaysmentioning
confidence: 99%
“…Amongst the best‐known small‐molecule MAO inhibitors, clorgyline (CL) confers good selectivity against MAO‐A, while known MAO‐B‐selective inhibitors include pargyline (PA), selegiline, and rasagiline . Some of these compounds are already being used in the treatment of various neurodegerative diseases . On the other hand, in order to selectively detect individual MAO enzymatic activities from cells and tissues, researchers have turned to the development of small‐molecule fluorogenic probes (SMFPs); of special note, two‐photon fluorogenic probes (TPFPs) when combined with advanced two‐photon fluorescence microscopy (TPFM) are able to penetrate tissues deeper and provoke less optical damage at a higher resolution than one‐photon fluorogenic probes (OPFPs) .…”
Section: Introductionmentioning
confidence: 99%
“…Monoamine oxidases (MAOs,EC 1.4.3.4) are a class of enzymes that deaminate a variety of amines. It is a flavin-containing amine oxidase due to the need for flavin adenine dinucleotide (FAD) as a cofactor. Many neurotransmitters are monoamines, and MAOs are responsible for their oxidative deamination to form the corresponding aldehyde to maintain a steady state of amine neurotransmitters in the brain. Based on the substrate preference and inhibitor specificities, MAOs can be differentiated into two isoforms, MAO-A and MAO-B (the sequence identity is approximately 70%), which are expressed at different levels in most mammalian tissues. The imbalance of the MAO-A is associated with neurological degeneration involving depression, anxiety, schizophrenia, and psychiatric disorders , Excess MAO-B activity often involves neurodegenerative diseases, such as Parkinson’s disease (PD) and Alzheimer’s disease (AD), and the inhibitors of MAOs have been clinically determined to delay the deterioration or relieve symptoms of these diseases. MAOs play an indispensable role in maintaining the balance of intracellular levels in biogenic amines; therefore, accurate detection of MAOs in the human cell and tissue samples is of great significance for further study of their function in related diseases and subsequent diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%